Knowledge Towards Immunization among Dentist of Bhopal City - Tiwari, Vidhatri; Saxena, Vrinda; Bhambhal, Ajay; Tiwari, Utkarsh; Singh, Aishwarya (Journal of Orofacial Research, 2012)
Introduction: Health care workers are at the particular risk of several vaccine preventable diseases due to lack of knowledge or casual attitude toward infection. Which leads to a substantial percentage of morbidity and mortality among patients and dentist as well. Materials and methods: Self-administered structured, coded questionnaire was distributed to 200 private practitioners and teaching staff in all the dental colleges in Bhopal city. Results: Half of them are HBV vaccinated and only 27% of them are aware regarding the viability of hepatitis B virus on a dry surface. Conclusion: The result of the present study revealed that dental practitioner has neglected attitude regarding the immunization and precaution to be taken for infected patients which may result in widespread exposure of patient and dentist to infections in the office and clinic.